Impedimetric detection of anticancer drug action on individual tumor cells using field-effect transistor devices - Susloparova, Anna; Justus Liebig University Giessen (My University, 2016)
This thesis describes an advancement in a new technique for measuring biological and electronic properties of individual cells on planar devices. The measuring principle of this technique is based on the impedance measurement of open-gate field-effect transistor (FET) devices. Due to the fact that the size of the transistor gate is comparable with the size of individual cells, FET devices can achieve a real single cell analysis. Thus, the application of FET devices for this technique can extend to cell cultures, which do not form confluent cell layers, such as nerve cells, individual cells of the immune system, etc. The aim of this work was to investigate the cell-substrate adhesion process at an individual cell level using FET devices and to develop and elaborate a model explanation for the spectra, since the cellular adhesion plays an important part for understanding cancer cell behaviour. We further used this technique to proof effects of anticancer drugs to individual tumor cells. In the context of this work, a new amplifier system was developed, which offered an increased bandwidth of the readout system and enabled measuring of impedance spectra at higher frequencies (up to 50 MHz). The impedance spectra recorded with this measurement setup were interpreted with an electrically equivalent circuit (EEC) model, for which an analytical expression was derived. The measured impedance spectra with the developed amplifier system were fitted with the derived analytical expression and cell-related parameters were extracted. The ability to extract the biological relevant data from these complex spectra might be very important for the future application of our novel technique in biological experiments. Moreover, we utilized this EEC model to extract the device-related parameters and to fabricate a new generation of FET devices with better performance in cell-substrate adhesion experiments. However, the FET devices based on silicon are complex, expensive to manufacture, and have the significant disadvantage in cell culture applications that they are not optically transparent. Due to this fact, devices based on organic semiconductor material were developed and fabricated in this work. The cellular adhesion experiments performed in this work eventually open up commercial opportunities for the Electrical Cell-substrate Impedance Sensing using field-effect transistors.

Diese Arbeit beschreibt eine Weiterentwicklung einer neuen Methode zur Messung biologischer und elektronischer Eigenschaften einzelner Zellen auf planaren Sensoren. Das Messprinzip dieses Verfahrens basiert auf der Impedanzmessung von open-gate Feldeffekttransistoren (FET). Aufgrund der Tatsache, dass die Größe eines Transistorgates mit der Größe der einzelnen Zellen vergleichbar ist, können die FET-Sensoren eine echte Einzelzellanalyse erreichen. Somit kann die Anwendung der FET-Sensoren für diese Technik auf die Zellkulturen erweitert werden, die nicht konfluenten Zellschichten bilden, wie beispielsweise Nervenzellen, einzelne Zellen des Immunsystems usw.Das Ziel dieser Arbeit war die Untersuchung des Zell-Substrat-Adhäsionsprozesses auf Einzelzellebene unter Verwendung von FET-Sensoren und die Entwicklung eines Modells, das die gemessenen Spektren erklärt, da die zelluläre Adhäsion eine wichtige Rolle für das Verständnis des Krebszellverhaltens spielt. Außerdem wurde diese Methode zum Nachweis der Wirkungsweise von Krebsmedikamenten auf einzelnen Tumorzellen verwendet.Im Rahmen dieser Arbeit wurde ein neues Verstärkersystem entwickelt, das eine erhöhte Bandbreite des Auslesesystems bietet und die Messung von Impedanzspektren bei höheren Frequenzen (bis 50 MHz) ermöglicht. Die gemessenen mit dem entwickelten Messaufbau Impedanzspektren wurden mit einem elektrischen Ersatzschaltbildmodell interpretiert. Für das entwickelte Ersatzschaltbildmodell wurde ein analytischer Ausdruck abgeleitet, mit dem die gemessenen Impedanzspektren gefittet und die zellbezogenen Parameter extrahiert wurden. Die Fähigkeit die biologisch relevanten Daten aus diesen komplexen Spektren zu extrahieren kann für die zukünftige Anwendung unserer neuartigen Technik in biologischen Experimenten sehr wichtig sein. Außerdem wurde das entwickelte Ersatzschaltbildmodell verwendet, um die devicebezogenen Parameter zu untersuchen und eine neue Generation von FET-Sensoren mit einer verbesserten Leistung in Zell-Substrat-Adhäsionsexperimente herzustellen.Jedoch sind die FET-Sensoren auf Siliziumbasis optisch nicht transparent, kompliziert und nicht kostengünstig in Herstellung. Aufgrund dieser Tatsache wurden die organischen elektrochemischen Transistoren in dieser Arbeit entwickelt und hergestellt. Die in dieser Arbeit durchgeführten Zelladhäsionsexperimente öffnen schließlich kommerzielle Möglichkeiten für die Electric Cell-Substrate Impedance Sensing Methode unter Verwendung von Feldeffekttransistoren.
Keywords: ddc:530